ECRH effect on the electric potential and turbulence in the TJ-II stellarator and T-10 tokamak plasmas. (21st June 2018) - Melnikov, A V; Krupnik, L I; Ascasibar, E; Cappa, A; Chmyga, A A; Deshko, G N; Drabinskij, M A; Eliseev, L G; Hidalgo, C; Khabanov, P O; Khrebtov, S M; Kharchev, N K; et al.
Abstract: Electric field Ε or electric potential φ plays a key role in the transport and turbulence of toroidal plasmas. It is believed that mean radial E r suppresses the turbulence eddies via E  ×  B shear, while oscillatory E r (zonal flows and geodesic acoustic modes, GAM) presents the mechanism of the turbulence self-regulation. Various aspects of the electron cyclotron resonance heating (ECRH), e.g. variation of power P ECRH value and deposition effect on the static and oscillatory components of potential were studied in two machines of similar size by heavy ion beam probe (HIBP), operating now on the T-10 tokamak and TJ-II stellarator. HIBP measures in a wide density range n ̄ e  = (0.3–5) × 10 19 m −3 and in various magnetic configurations in Ohmic and ECRH plasmas on T-10, and in ECRH and NBI-heated plasmas on TJ-II. With ECRH, the potential evolves towards the positive direction. This extra potential Δ φ increases with P ECRH increase, while Δ φ decreases with plasma density raise. ECRH excites the broadband electrostatic oscillations in low-density TJ-II plasma, while in high-density T-10 plasma, this effect is opposite. In T-10 GAM frequency f GAM increases with P ECRH in accordance with theoretical dependence on electron temperature ( f GAM  ∼  T e 1 / 2 ), and GAM amplitude increases with P ECRH . ECRH affects to NBI-excited Alfvén eigenmodes (AEs): the steady frequency AEs transform to the chirping modes. In the low-density TJ-II plasmas, strong ECRH produces suprathermal (ST) electrons, exciting the electrostatic ST-modes. Dual HIBP measures the stable long-range potential correlations in TJ-II, resembling spatially localized low-frequency zonal flows in the core of ECRH plasmas. Finally, various aspects of the ECRH effects on the mean potential, broadband electrostatic turbulence, and on quasicoherent modes, including GAMs, AEs and ST-modes, are summarized.